The Federal Tax Implications of Bush v. Gore - Paul L. Caron (Washington University Law Quarterly, 2001)
Part I reviews the pre-Bosch confusion regarding how much deference federal courts should give to prior state court decisions in federal tax litigation. Federal courts used and advocated a wide variety of approaches during this period, none of which properly accommodated the underlying revenue and comity interests. Part I then turns to the Bosch decision and the original promise of the “proper regard” standard as a way to balance these competing concerns. Part II explains how in practice federal courts have converted this “proper regard” deference standard into a de novo standard of review. Over one thousand federal court cases have cited Bosch over the past thirty-four years, and courts in a clear majority of those cases in which the taxpayer was involved in prior state court litigation have refused to follow the state court’s interpretation of state law in the federal tax proceeding. As a result, the federal courts, in practice, have converted the “proper regard” standard into a license to give “no regard” to state court decisions on state law. Part III discusses the recent Bush v. Gore decision and argues that it is inconsistent with this “no regard” approach. The enormous interest generated by the Bush v. Gore decision makes this a particularly propitious time to rethink this nettlesome question of federal tax law. Part IV argues that the Erie doctrine provides the best vehicle for reconciling Bosch with Bush v. Gore. The complete-deference approach originally embraced by the Supreme Court and recently resurrected by commentators exalts the Bush v. Gore comity interest at the expense of the federal revenue interest. The nonadversary proceeding test adopted by the Internal Revenue Service (the Service) and commentators in recent years inevitably degenerates into a pointless inquiry into the requisite degree of adversariness necessary to make a lower state court decision on state law controlling in subsequent federal tax litigation. Procedural devices such as federal court certification of state law questions to state courts and joinder of the Service in the state court action also do not provide a workable solution to this intractable problem. This Article rejects the “no regard” approach in the existing case law and instead contends that a federal court should apply the same standard of review to a state court decision as would have been applied had the decision been appealed in the state court system. This “bottom-up” approach is consistent with recent cases and commentary on the Erie doctrine. This revitalization of the “proper regard” standard allows federal courts to protect the federal revenue interest without undermining the comity concern by allowing state courts, in most situations, to be the final arbiter of state law. Only in the rare tax equivalent of the Bush v. Gore case should federal courts step in and overturn a state court’s application of state law.
Keywords: Taxation; Federal courts; Federal government; Bush v. Gore 531 U.S. 98 (2000); Commissioner v. Estate of Bosch 387 U.S. 456 (1967); Judicial review; Tax law